Pulse wave analyzed cardiovascular parameters in young first degree relatives of type 2 diabetics- a cross-sectional study - Jayesh D. Solanki; Hemant B. Mehta; Chinmay J. Shah (Indian Heart Journal, 2018)
Background: First degree relatives (FDR) of type 2 diabetic (T2D) are predisposed for type 2 diabetes mellitus (T2DM) which accelerates cardiovascular aging. Pulse wave analysis (PWA) gives non-invasive measurement of central hemodynamics like central blood pressure (cBP), cardiac output (CO), stroke work (SW) and vascular stiffness like pulse wave velocity (PWV) and augmentation index at heart rate 75 (AIx@75). Objective: To study PWA derived cardiovascular parameters in FDRs of T2D as compared to controls. Materials and methods: We enrolled 117 FDRs of T2D and 117 matched controls for a cross-sectional study. We performed PWA using Mobil-o-Graph (IEM, Germany) by oscillometric method to derive cardiovascular parameters which were compared and correlated for significance. P value less than 0.05 was considered statistically significant. Results: Gender, age, height, weight, body mass index (BMI), physical activity were comparable between groups. FDRs of T2D had significantly higher blood pressure (brachial-systolic 125 vs 118, diastolic 80 vs 77, mean 100 vs 96 mmHg and central- systolic 113 vs 105, diastolic 82 vs 79, pulse pressure 31 vs 28 mmHg), SW (98 vs 90 g m/bt), rate pressure product (RPP- 113 vs 107), PWV (5.14 vs 4.89 m/s), AIx@75 (30 vs 27) than control. Dependant variables correlated with brachial BP more than age or anthropometric variables. Result did not differ by maternal or paternal inheritance in case group. Conclusions: Young, sedentary, non-obese FDRs of T2D have adverse cardiovascular profile which is suggested to worsen before or with onset of T2DM and definitely need attention for life style modification as primary prevention. Keywords: Cardiovascular, First degree relative, Oscillometric, Pulse wave analysis, Type 2 diabetes mellitus